Restaurant authenticity and purchasing intentions: the mediating role of social contagion - Pinto, Maria Madalena Mouro Ferreira Abranches (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence